Electro–dynamic Forces in Conductor of Spiral Shape - V. V. Pavlovets; A. S. Gerasimovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains vector-parametric equation of a spiral, expressions for calculation of the magnetic field induction established by an electrical conductor of a spiral shape, and also radial and tangential forces acting per unit of a conductor length. Calculation data on distribution and values of electro-dynamic forces in separate turns are given in the paper. The paper also shows a change in direction of electro-dynamic force action in the outward turn of the spiral conductor.